POWER DYNAMICS AND REPRESENTATION IN COETZEE’S WAITING FOR THE BARBARIANS AND FOE: A COMPARATIVE ANALYSIS (Contemporary Journal of Social Science Review, 2024)
This paper deals with a comparative reading of J.M. Coetzee’s Waiting for the Barbarians (1980) and Foe (1986) in terms of power and representation. This research exposes through representations, how the two novels are informed by and undermine the ways in which dominant spaces assert and maintain power. At the heart of the discussion lies Coetzee’s critique of colonial authority and its narrative control mechanisms. The unnamed Magistrate in Waiting for the Barbarians struggles to reconcile his complicity in an oppressive colonial order with the moral imperative to resist it by exposing how the ‘barbarian’ is rendered sub-human and the kind of violence that is implicated in imperial projections of power. While Foe questions the silencing of subaltern voices, particularly through Friday, whose muteness embodies the erasure of subaltern points of view in canonical literature.  It also touches on the interstitially of language and silence in Coetzee’s writing, showing how Coetzee subverts conventional narratives to resolve ethical dilemmas about voice and agency. If Waiting for the Barbarians punches on the spectacle of imperial violence then Foe tracks the less overt, more insidious power of authorship and narrative manipulation. Collectively, these novels shed light on Coetzee’s larger preoccupations with justice, ethical engagement and the politics of narrative. Through this comparative framework, the analysis sheds light on how Coetzee’s oeuvre interrogates the limits and potential of representation and illuminates the ways in which literature can challenge and disrupt systems of power.